MALE GENDER STEREOTYPES IN PAKISTANI ADVERTISEMENTS - Mirza, Zainab Kamran (PEOPLE: International Journal of Social Sciences, 2016)
This paper deals with the study of how men are portrayed and perceived in television commercials in electronic media. After reviewing existing literature on gender stereotypes and in advertisements, a research gap has been identified in the field of gender stereotype studies in electronic media: male gender stereotypes and their utilization in advertisements. Hence, this research combines these aspects in an attempt to fill the aforementioned gap. Content analysis is chosen as a method to evaluate male gender stereotypes, if any. The analysis of the study is comprised 60 ads which were further coded for nine distinguished categories and sub-categories. The outcome of this study supports the proposed hypothesis. Stereotypes of male gender roles exist today in our society and dominate the overall portrayal.